Maximum Demand Reduction (MDRed) modelling using MATLAB Stateflow - Subramani G.; Ramachandaramurthy V.K. (Institute of Physics, 2024)
Based on renewable energy case studies, the MDRed (Maximum Demand Reduction) Model is created as an optimization apparatus for the solar PV-battery system. In this paper, MATLAB modeling toolbox is used for simulation of the solar PV-BESS design and verification of the MDRed modeling via variations in MD limit and solar PV load. Based on MDRed model, the maximum demand supervisory control algorithm is developed via MATLAB Stateflow for the battery management system (BMS) to monitor and regulate the load to maintain the net load consumption below MD limit with the solar PV system. In summary, the simulation with the master MD controller shows the effectiveness of the proposed controller on the BMS to cater to MD reductions during solar irradiance and load pattern variations. Published under licence by IOP Publishing Ltd.